Three-Dimensional Integrated Circuit Design EDA, Design and Microarchitectures - Xie, Yuan; Cong, Jingsheng Jason; Sapatnekar, Sachin (Integrated Circuits and Systems, 2010)
This book presents an overview of the field of 3D IC design, with an emphasis on electronic design automation (EDA) tools and algorithms that can enable the adoption of 3D ICs, and the architectural implementation and potential for future 3D system design. The aim of this book is to provide the reader with a complete understanding of: the promise of 3D ICs in building novel systems that enable the chip industry to continue along the path of performance scaling, the state of the art in fabrication technologies for 3D integration, the most prominent 3D-specific EDA challenges, along with solutions and best practices, the architectural benefits of using 3D technology, architectural-and system-level design issues, and the cost implications of 3D IC design. Three Dimensional Integrated Circuit Design: EDA, Design and Microarchitectures is intended for practitioners in the field, researchers and graduate students seeking to know more about 3D IC design.